Role of Nanoparticles on the Alleviation of Abiotic Stress Tolerance: A Review - Rajasreelatha V.; Thippeswamy M. (Journal of Stress Physiology & Biochemistry, 2023)
Nanotechnology has become a dynamically demand driven developing industry with a multiple applications in material manufacturing, computer chips, medical diagnosis, energy and health care, cancer therapy, targeted drug delivery, electronics, cosmetic industry, biosensors and crop improvement. It was estimated that by year 2014, more than 15% of all products in the global market will have some kind of nanotechnology incorporated into their manufacturing process. Nanoparticles penetrate into specific cellular locations because of their extreme small size and acquired some peculiar properties play significant role in the protection of plants against various abiotic stresses. The application of nanoparticles increased germination and seedling growth, physiological activities including photosynthesis and nitrogen metabolism, leaf activities of CAT, POX and APX, chlorophyll contents, protein, carbohydrate contents and yield, and also positive changes in gene expression indicating their potential use in crop improvement. Nanoparticles enhances the water stress tolerance via enhancing root hydraulic conductance and water uptake in plants and showing differential abundance of proteins involved in oxidation-reduction, ROS detoxification, stress signalling, and hormonal pathways. Proteomic techniques have contributed substantially in understanding the molecular mechanisms of plant responses against various stresses by providing a link between gene expression and cell metabolism. As the coding regions of genome are responsible for plant adaptation to adverse conditions, protein signatures provide insights into the nanoparticles at proteome level. The recent contributions of plant proteomic research to elaborate the complex molecular pathways and the mobility of the nanoparticles is very high, which leads to rapid transport of the nutrient to all parts of the cultivated plants with the use of nano preparations in stressful conditions.